Concurrent synthesis of SnO/SnO2 nanocomposites and their enhanced photocatalytic activity - Roy, Animesh; Arbuj, Sudhir; Waghadkar, Yogesh; Shinde, Manish; Umarji, Govind; Rane, Sunit; Patil, Kashinath; Gosavi, Suresh; Chauhan, Ratna (Journal of Solid State Electrochemistry, 2017)
The SnO/SnO2 nanocomposites were synthesized using semisolvothermal reaction technique. These nanocomposites were prepared using different combination of solvents viz., ethanol, water, and ethylene glycol at 180 A degrees C for 24 h. The synthesized nanocomposites were analyzed with various characterization techniques. Structural analysis indicates the formation of tetragonal phase of SnO2 for the sample prepared in ethanol, whereas for other solvent combinations, the mixture of SnO and SnO2 having tetragonal crystal structures were observed. The optical study shows enhanced absorbance in the visible region for all the prepared SnO/SnO2 nanocomposites. The observed band gap was found to be in the range of 3.0 to 3.25 eV. Microstructural determinations confirm the formation of nanostructures having spherical as well as rod-like morphology. The size of nanoparticles in ethanol-mediated solvent was found to be in the range of 5 to 7 nm. Thermogravimetric analysis indicate the weight gain around 1.3 wt% confirming the conversion of SnO to SnO2 material. The photocatalytic activity of synthesized nanocomposites was evaluated by following the aqueous methylene blue (MB) degradation. The sample prepared in ethylene glycol-mediated solvent showed highest photoactivity having apparent rate constant (K-app) 0.62 x 10(-2) min(-1).
Keywords: Dye-degradation; Nanocomposite; Photocatalysis; tin oxide

Nonenzymatic glucose detection in human serum using Ni nanoparticles decorated reduced graphene oxide - Waichal, Rupali; Bhirud, Ashwini; Fouad, H.; Gosavi, Suresh; Ashokkumar, Muthupandian (Science of Advanced Materials, 2020)
Reduced Graphene oxide (RGO) decorated with Ni nanoparticles (NiNPs) composites, have been successfully synthesized using a simple hydrothermal method and possessing excellent electrocatalytic activity towards glucose oxidation. The morphological and structural features of RGO-Ni nanocomposites were characterized by field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS) and energy dispersive spectroscopy (EDS). From TEM, we observed that NiNPs were anchored on RGO sheets. Cyclic Voltammetric (CV) study revealed that the electrocatalytic activity of RGO-Ni nanocomposite with 20% Ni loading (RGONi-20) towards glucose oxidation is better than that shown by bare Glassy Carbon Electrode (GCE), RGO, bare NiNPs, RGONi10 and RGONi-30. The prepared nanocomposites exhibited fast electrocatalytic response (<5 s) towards glucose oxidation. Amperometric study indicates that the present glucose sensor have exhibited excellent performance by offering a lowest detection limit as 5.1 mu M, with linier range from 2 to 5000 mu M and high sensitivity of 896.67 mu A mM(-1) cm(-2). Interference from different anticipatable electroactive substances such as ascorbic acid (AA), uric acid (UA) and dopamine (DA) is not observed. Furthermore, the application of the as prepared sensor was successfully demonstrated for the detection of glucose in human serum and results were comparable to presently used nonenzymatic technique. RGONi-20 nanocomposite electrode holds great promise for the development of biosensors and other electrochemical devices.
Keywords: Electrochemical; Glucose Sensor; Graphene-Nickel Nanoparticles; hydrothermal; Nanocomposite; Nonenzymatic